Moderasi Beragama pada Masyarakat Kelurahan Pulo Brayan Kota - Zainun Zainun; Aldi Koto; Syopiah Syopiah; Yolanda Ruchiyani; Ayu Nurjannah (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
The Indonesian nation is a culturally diverse society with its plurality. Diversity includes differences in culture, religion, race, language, ethnicity, tradition and so on. In such a multicultural society, tensions and conflicts often occur between religious groups and have an impact on the harmony of life. The purpose of this paper is to discuss religious moderation in the diversity of religious communities in Pulo Brayan Kota urban village. Religious understanding is a historical fact in building religious moderation, namely building community moderation in religious life in the Pulo Brayan City community by maintaining community togetherness, which is part of the right to life, the right to maintain honor. Thus, it needs support from various groups, so that it can improve the paradigm of thinking that is fundamentally based on the principle of religion. What is meant is an activity to conduct a review in the activities of religious life, so as not to deviate from the applicable rules that have been set by the religious law of each. its adherents, especially the moderation of religious communities in the field of faith, worship, and moderation in the field of law so that openness, tolerance and respect for religions are the most important aspects of human life.